Effect of Zoledronic Acid and Denosumab in Patients With Low Back Pain and Modic Change: A Proof‐of‐Principle Trial. (2nd February 2018) - Cai, Guoqi; Laslett, Laura L; Aitken, Dawn; Halliday, Andrew; Pan, Feng; Otahal, Petr; Speden, Deborah; Winzenberg, Tania M; Jones, Graeme
ABSTRACT: The aim of this study was to evaluate the effect of zoledronic acid (ZA) and denosumab on low back pain (LBP) and Modic change (MC) over 6 months. Adults aged ≥40 years with significant LBP for at least 6 months duration and MC (type 1, 2, or mixed) were randomized to receive ZA (5 mg/100 mL), denosumab (60 mg), or placebo. LBP was measured monthly by visual analogue scale (VAS) and the LBP Rating Scale (RS). MC was measured from MRIs of T12 –S1 vertebrae at screening and 6 months. A total of 103 participants with moderate/severe LBP (mean VAS = 57 mm; mean RS = 18) and median total MC area 538 mm 2 were enrolled. Compared to placebo, LBP reduced significantly at 6 months in the ZA group for RS (–3.3; 95% CI, –5.9 to –0.7) but not VAS (–8.2; 95% CI, –18.8 to +2.4) with similar findings for denosumab (RS, –3.0; 95% CI, –5.7 to –0.3; VAS, –10.7; 95% CI, –21.7 to +0.2). There was little change in areal MC size overall and no difference between groups with the exception of denosumab in those with type 1 Modic change (–22.1 mm 2 ; 95% CI, –41.5 to –2.7). In post hoc analyses, both medications significantly reduced VAS LBP in participants with milder disc degeneration and non‐neuropathic pain, and denosumab reduced VAS LBP in those with type 1 MC over 6 months, compared to placebo. Adverse events were more frequent in the ZA group. These results suggests a potential therapeutic role for ZA and denosumab in MC‐associated LBP. © 2018 American Society for Bone and Mineral Research.